2014
DOI: 10.1186/1475-2891-13-28
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic compounds appear to limit the nutritional benefit of biofortified higher iron black bean (Phaseolus vulgarisL.)

Abstract: BackgroundOur objective was to determine if a biofortified variety of black bean can provide more bioavailable-iron (Fe) than a standard variety. Two lines of black beans (Phaseolus-vulgaris L.), a standard (DOR500; 59μg Fe/g) and biofortified (MIB465; 88μg Fe/g) were used. The DOR500 is a common commercial variety, and the MIB465 is a line developed for higher-Fe content. Given the high prevalence of Fe-deficiency anemia worldwide, it is important to determine if Fe-biofortified black beans can provide more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
154
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(168 citation statements)
references
References 39 publications
11
154
3
Order By: Relevance
“…A recent study with Fe-deficient broiler chickens showed that iron-fortified black beans produced limited Fe dietary benefit (i.e., improved Fe status), likely due to the presence of high levels of polyphenols in black bean seed coats. 17 Similarly, higher iron bioavailability from white beans compared with red beans was demonstrated in a feeding trial with week-old chicks, again implicating the role of higher polyphenolic content in red beans for the decrease in iron nutrition. 15 In vitro models using cultured human intestinal cells have been shown to be useful for a more focused investigation of the absorption of dietary compounds.…”
Section: ■ Introductionmentioning
confidence: 92%
“…A recent study with Fe-deficient broiler chickens showed that iron-fortified black beans produced limited Fe dietary benefit (i.e., improved Fe status), likely due to the presence of high levels of polyphenols in black bean seed coats. 17 Similarly, higher iron bioavailability from white beans compared with red beans was demonstrated in a feeding trial with week-old chicks, again implicating the role of higher polyphenolic content in red beans for the decrease in iron nutrition. 15 In vitro models using cultured human intestinal cells have been shown to be useful for a more focused investigation of the absorption of dietary compounds.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Developing staple food crops for enhanced nutritional quality often requires high throughput methods capable of examining hundreds and sometimes thousands of samples [11,12,13,14]. In general, for Zn and provitamin A, the content of these micronutrients has been more positively correlated with enhanced nutritional quality; whereas for Fe, enhanced content does not always equate to improved nutritional quality [15,16,17,18,19]. Understanding the factors related to the bioavailability of Fe may therefore be the key to developing sustainable Fe-biofortified crops, hence, the development of the appropriate screening tools is vital to properly guide the crop breeding process.…”
Section: Introductionmentioning
confidence: 99%
“…Data from four trials (3 bean and 1 pearl millet) using the above-mentioned screening tools is discussed and analyzed relative to the parallel human efficacy studies [11,15,16,17,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations